Bound by their Lisbon legacy - Hayes, Ella (Harlequin romance, 2024)
"Will never expected to find himself in Lisbon. And the last person he wants to be there with is Quinn! He hasn't talked to his deceased father's ward since they were teenagers, when their relationship was, well...tense. Now, to secure the legacy that's been left to them, they need to restore a derelict hotel. But first they must learn to work together. And ignore the newfound fireworks exploding into passionate life between them!"--back cover.